Evaluation of molt induction using cassava meal varying the length of feeding period in older (90 week) laying hens. (27th March 2019) - Chanaksorn, M; Boonkaewwan, C; Kayan, A; Gongruttananun, N
ABSTRACT: Physiological changes during molt and postmolt egg production variables were compared among hens induced to molt by using cassava meal varying the length of the feeding period. Hens were randomly assigned to 3 treatments of 72 birds each: 1) molted by full feeding with cassava meal for 4 wk (CAS4 ); 2) molted by full feeding with cassava meal for 5 wk (CAS5 ); and 3) molted by full feeding with cassava meal for 6 wk (CAS6 ). All groups were fed a pullet developer diet for 2 wk following treatment. During the molt period, the birds were exposed to an 8L:16D photoperiod and had access to drinking water at all times. Thereafter, all hens were fed a layer diet (17.71% CP), and exposed to a 16L:8D photoperiod, and production performance was measured for 16 wk. The molt treatments resulted in total cessation of egg production in all treatments within 2 wk following feeding of the molt diet. BW loss of birds in the CAS6 treatment was approximately 41.81%, which was significantly higher ( P < 0.05) than those in the CAS5 (37.63%) and CAS4 (31.89%) treatments. The CAS5 and CAS6 hens had significantly lower ( P < 0.05) ovarian and oviducal weights than the CAS4 hens. No consistent differences were observed for concentrations of plasma estradiol and progesterone, bone quality, or mortality among the treatments. Postmolt feed consumption, egg weight, and mortality were not different ( P > 0.05) as a result of molt induction method. However, the CAS4 hens had significantly higher ( P < 0.05) cumulative egg production and lower feed conversion ratio than hens in the CAS6 treatment. Significant differences were found among treatments for Haugh units and shell thickness in some periods of the postmolt. It was concluded that cassava meal could be used to induce molt in laying hens effectively, feeding the molt diet for 4 wk produced optimum body weight loss and postmolt performance.